COGNITIVE SOVEREIGNTY IN MULTIMODAL AI CLASSROOMS: ARE WE STILL THINKING FOR OURSELVES? (SCIENCE TIME JOURNAL, 2026)
The rapid integration of multimodal artificial intelligence (AI) into educational environments has transformed the nature of teaching, learning, and intellectual engagement. Multimodal AI systems, capable of processing and generating text, audio, images, video, and interactive dialogue, are increasingly functioning as cognitive partners in classrooms. While these technologies offer unprecedented opportunities for personalized learning, accessibility, and educational efficiency, they also raise critical concerns regarding cognitive sovereignty — the capacity of individuals to maintain independent control over their own thinking processes. This article examines the philosophical, educational, and ethical implications of AI-mediated learning, focusing on cognitive offloading, algorithmic influence, intellectual dependency, and the evolving purpose of education. The study argues that although multimodal AI can augment human cognition, excessive reliance on AI-generated reasoning risks weakening critical thinking, creativity, and reflective autonomy. The article concludes that preserving cognitive sovereignty requires educational systems to prioritize critical inquiry, AI literacy, ethical awareness, and process-oriented learning models that strengthen rather than replace human intellectual agency.